Professional wellbeing and turnover intention among child therapists: a comparison between therapists trained and untrained in Trauma-Focused Cognitive Behavioral Therapy - Samira Aminihajibashi; Ane-Marthe Solheim Skar; Tine K. Jensen (BMC, 2022)
Abstract Background Poor professional wellbeing and job turnover is challenging for child mental health clinics and despite an increasing interest in implementing evidence-based practices (EBPs) in mental health services, little is known about if and how using EBPs may influence therapists' professional wellbeing and turnover intention. To investigate this, we compare the average level of compassion satisfaction, burnout, secondary traumatic stress, and turnover intention between therapists trained in an EBP (Trauma-Focused Cognitive Behavioral Therapy - TF-CBT) and untrained therapists. We also explore the prevalence of and the associations between these personal and organizational outcomes. Method In this cross-sectional study, the data is collected from a national sample of 373 therapists 5 years after an implementation program began (i.e., in the sustainment phase). The variables were measured by the Professional Quality of Life and the Turnover Intention Scales. The Evidence-Based Practice Attitude Scale was also used to measure therapists' attitudes toward EBPs. Results Over 70% of the respondents reported medium to high levels of burnout, secondary traumatic stress symptoms, and compassion satisfaction, whereas one-third of the respondents reported a high level of intention to leave their job in the current or near future. Higher ratings on burnout and secondary traumatic stress were significantly associated with lower compassion satisfaction and higher turnover intention. Finally, we found significantly lower degree of burnout and turnover intention along with higher compassion satisfaction among TF-CBT therapists (n = 96), compared to other therapists who were not trained in TF-CBT (n = 231). These differences could not be explained by between-group differences in age, job tenure, educational background, or therapists' attitudes towards EBPs. However, mean differences in ratings on secondary traumatic stress symptoms were not statistically significant. Conclusion Although the prevalence findings are in general alarming, the present study provides the first empirical evidence for a potential positive effect of being trained in TF-CBT on therapists' wellbeing and turnover intention. We discuss these findings in the light of self-efficacy theory and the job demands-resources model.